Evaluation of the Protective Effects of Quercetin, Rutin, Naringenin, Resveratrol and Trolox Against Idarubicin-Induced DNA Damage - Haydar Çelik; Emel Arinç (Journal of Pharmacy & Pharmaceutical Sciences, 2010)
PURPOSE. Idarubicin is a synthetic anthracycline anticancer drug widely used in the treatment of some hematological malignancies. The studies in our laboratory have clearly demonstrated that idarubicin can undergo reductive bioactivation by NADPH-cytochrome P450 reductase to free radicals with resulting formation of DNA strand breaks, which can potentially contribute to its genotoxic effects [Çelik, H., Arinç, E., Bioreduction of idarubicin and formation of ROS responsible for DNA cleavage by NADPH-cytochrome P450 reductase and its potential role in the antitumor effect. J Pharm Pharm Sci, 11(4):68-82, 2008]. In the current study, our aim was to investigate the possible protective effects of several phenolic antioxidants, quercetin, rutin, naringenin, resveratrol and trolox, against the DNA-damaging effect of idarubicin originating from its P450 reductase-catalyzed bioactivation. METHODS. DNA damage was measured by detecting single-strand breaks in plasmid pBR322 DNA using a cell-free agarose gel method. RESULTS. Our results indicated that, among the compounds tested, quercetin was the most potent antioxidant in preventing DNA damage. Quercetin significantly decreased the extent of DNA strand breaks in a dose-dependent manner; 100 μM of quercetin almost completely inhibited the DNA strand breakage. Unlike quercetin, its glycosidated conjugate rutin, failed to provide any significant protection against idarubicin-induced DNA strand breaks except at the highest concentration tested (2 mM). The protective effects of other antioxidants were significantly less than that of quercetin even at high concentrations. Quercetin was found to be also an effective protector against DNA damage induced by mitomycin C. CONCLUSION. We conclude that quercetin, one of the most abundant flavonoids in the human diet, is highly effective in reducing the DNA damage caused by the antitumor agents, idarubicin and mitomycin C, following bioactivation by P450 reductase.